Syllable Structure Universals and Native Language Interference in Second Language Perception and Production: Positional Asymmetry and Perceptual Links to Accentedness - Cheng, Bing; Zhang, Yang (Frontiers in Psychology, 2015)
The present study investigated how syllable structure differences between the first Language (L1) and the second language (L2) affect L2 consonant perception and production at syllable-initial and syllable-final positions. The participants were Mandarin-speaking college students who studied English as a second language. Monosyllabic English words were used in the perception test. Production was recorded from each Chinese subject and rated for accentedness by two native speakers of English. Consistent with previous studies, significant positional asymmetry effects were found across speech sound categories in terms of voicing, places of articulation, and manner of articulation. Furthermore, significant correlations between perception and accentedness ratings were found at the syllable onset position but not for the coda. Many exceptions were also found, which could not be solely accounted for by differences in L1-L2 syllabic structures. The results show a strong effect of language experience at the syllable level, which joins force with acoustic, phonetic, and phonemic properties of individual consonants in influencing positional asymmetry in both domains of L2 segmental perception and production. The complexities and exceptions call for further systematic studies on the interactions between syllable structure universals and native-language interference and refined theoretical models to specify the links between perception and production in second language acquisition.